Dietetics students' experiences of dietetics workforce preparation and preparedness: a systematic review and qualitative synthesis. Issue 2 (16th October 2018) - Morgan, K.; Campbell, K. L.; Reidlinger, D. P.
Abstract: Background: Dietetics students are a widely researched group. As emerging dietitians, they can provide valuable insights to inform how dietetics education programmes may be enhanced to meet contemporary healthcare needs. This review aimed to systematically synthesise dietetics students' experiences of dietetics workforce preparation. Methods: MEDLINE, CINAHL, Embase, PsycINFO, ERIC, Informit and ProQuest Dissertations and Theses Global were searched to identify research published until June 2017. Studies investigating dietetics students' experiences of dietetics workforce preparation, and employing qualitative data collection and analysis methods were included. Data analysis was guided by thematic synthesis, where themes were constructed through an iterative and inductive process. Study quality was appraised using the RATS Qualitative Research Review Guidelines. Results: From the 3301 records identified, five studies met the inclusion criteria and the views of 120 dietetics students from two countries over a 9‐year period were synthesised. The overarching theme of 'navigating through the ups and downs' was underpinned by four main themes: enduring hurdles; reconciling expectations; transforming self; and making and breaking connections. Quality appraisal results rated selection bias as being inadequate/inappropriate across all studies. Conclusions: Dietetics students undertake a transformational journey through dietetics education. They are inspired by seeing what is possible through meaningful encounters with practitioners in diverse settings. However, they are challenged by competitive environments and perceived ideals that are embedded in the profession. Strategies that focus on exposing dietetics students to inspirational practitioners, increasing and celebrating diversity in academic/placement settings, and incentivising collaboration across dietetics education, could act as catalysts to enhance the experience of future dietetics students and the nutrition‐related health of those they will serve.